Pengaruh pendidikan kewirausahaan terhadap minat dan kemampuan mahasiswa dalam memulai usaha sendiri - Salafudin, Afif; Khadafi, Moammar; Yandi, Makhtum; Nafis, Ahmad Rizqon (Maliki Interdisciplinary Journal, 2024)
This research aims to investigate the influence of entrepreneurship education on students’ interest and ability in starting their own business. Entrepreneurship is becoming increasingly important in the global economy, and students are considered a potential resource who can contribute to economic growth through their independent efforts. However, success in starting your own business depends not only on technical knowledge, but also on motivation and entrepreneurial skills. The results of this research provide important insight into the importance of entrepreneurship education programs in preparing students to become entrepreneurs. In the context of higher education, universities can play a more active role in developing students’ entrepreneurial interests and skills. The implication of this research is the need to improve entrepreneurship education programs and integrate entrepreneurship into the academic curriculum to encourage entrepreneurial interest and abilities among students